The influence of Naval Arms limitation on U.S. Naval innovation during the interwar period, 1921 - 1937 - Kuehn, John Trost (Kansas State University, 2007)
This dissertation examines the influence of the treaty system inaugurated at the Washington Naval Conference of 1921-22 upon innovation in the design of the interwar U.S. fleet. The way in which sea power was viewed by the U.S. Navy of the period combined with the Navy’s unique organizational structure to shape the Navy’s efforts in building a “treaty fleet.” In particular, the General Board of the Navy, a formal body established by the Secretary of the Navy to advise him on both strategic and other matters with respect to fleet, served as the organizational nexus for the interaction between fleet design and treaty implementation. The General Board members orchestrated the efforts by the principal Naval Bureaus, the Naval War College, and the Office of the Chief of Naval Operations in ensuring that the designs adopted for the warships built and modified during the period of the Washington (Five Power) and London Naval Treaties both met treaty requirements while meeting strategic needs. The leadership of the Navy at large, and the General Board in particular, felt themselves especially constrained by Article XIX (the fortification clause) of the Five Power Treaty that implemented a status quo on naval fortification in the Western Pacific. The treaty system led the Navy to design a measurably different fleet than it might otherwise have done in the absence of naval limitations.
Keywords: U.S. Navy; Arms Limitation; Washington Naval Treaty; General Board of the Navy; Military Innovation; History, United States (0337)